Influencia del polimorfismo genético rs2927488 de Bcl3 en el síndrome de intestino irritable - Maureira, Valeria; Vera , Daniela; Pérez N., Claudio; Lomasney, Kevin Lomasney; Pérez de Arce, Edith; Madrid, Ana María; Beltrán M., Caroll (Revista Hospital Clínico Universidad de Chile, 2015)
Irritable Bowel Syndrome (IBS) is a functional disorder characterized by abdominal discomfort associated with changes in bowel habit and increased intestinal sensitivity. It is one of the most common disorders of digestive health in Chile as well as in the world. Although the pathophysiological mechanisms of IBS have yet to be fully established, it is known that (epi-) genetic factors are involved in the development of the disorder. Bcl3 (B-cell leukemia/lymphoma 3) is a regulatory protein of the intestinal inflammatory response, specifically, with regard to the signaling pathways of NF-kB (Nuclear Factor-kB). Among the variability of the human genome, the gene encoding Bcl3 contains the polymorphism SNPs rs2927488 (variants A/G) which has been associated with susceptibility to developing Inflammatory Bowel Disease (IBD). Furthermore, the presence of this polymorphic variant has been correlated with increasedlevels of Bcl3 gene expression in patients with Crohn’s Disease. Our laboratory is focused on understanding the potential relationship between Bcl3 and IBS. Our preliminary studies describe an increased expression of Bcl3 at the intestinal mucosal epithelium in IBS patients with a diarrheal-phenotype (IBS-D). We are now interested to investigate if the presence of the variant SNP rs2927488(A/G) is a susceptibility factor for IBS development and to understand the significance of its relationship with Bcl3 expression, in Chilean IBS patients. In this review, we focus primarily on the relationship between rs2927488(A/G) polymorphism of Bcl3 gene, its protein expression and its mechanisms of control over the inflammatory response.